Variasi Media Tanam Terhadap Pertumbuhan Pakcoy (Brassica rapa L.) Dengan Metode Hidroponik Sistem Deep Flow Technique (DFT) - Arzita Arzita; Muhammad Hery Setiawan; Mapegau Mapegau; Addion Nizori (Jurnal Media Pertanian, 2023)
Pakcoy is a popular vegetable in Indonesia because it tastes good, is high in nutrition, and contains dietary fiber, which aids in digestion. Pakcoy cultivation is possible using hydroponic technology, which uses water as a nutrient medium for plants. The Deep Flow Technique is one type of hydroponic technology that is being developed (DFT). The DFT hydroponic system is a culture method that uses water as a medium to provide nutrients. This study had seven stages: creating a hydroponic installation, creating planting media, sowing pakcoy seeds, transplanting pakcoy, providing nutrient water, plant maintenance, and harvesting. This study used a completely randomized design (CRD) with 7 treatments and 3 repetitions. Plant height (cm), number of leaves (strands), and plant fresh weight were all measured (g). Differences in planting media had a significant effect on pakcoy growth, according to the research results. Pakcoy plants grew best on the coconut coir + fern root growing medium, with a plant height of 22.90 cm, 20.33 leaves, and a fresh weight of 77.67 g.